Thrombotic Microangiopathy in the Postpartum Period (Literature Review, Clinical Case Report) - L. Markin; K. Shatylovych; S. Serhiichuk; H. Kunynets; M. Lysyi (Львівський клінічний вісник)
Introduction. Thrombotic microangiopathy (TMA) is a heterogeneous group of diseases that, in the presence of endothelial damage, can lead to microvascular thrombosis, secondary platelet consumption, mechanical hemolysis and ischemic end-organs damage.